SCIENCE-INDUSTRY COOPERATION: THE ISSUES OF PATENTING AND COMMERCIALIZATION - Elisaveta Somova (European Scientific Journal, ESJ, 2015)
Advancement of science-industry cooperation is a popular trend in modern world. Developed and developing countries try to boost their economy’s growth by the transferring of knowledge between scientists and businesses. Intellectual property transfer is the central area of cooperation between scientific organizations and businesses. It takes place mainly by patent licenses as it allows dissemination of technology to the private sector at market price. Governments may incent researchers to license their inventions by economic stimulus as well as determine conditions – patent regime – on which new technologies are transferred. Undoubtedly, success of science-industry cooperation also depends on research institutions’ innovative policies – their practical approaches towards licensing. Nowadays we could distinguish two commercialization models - supply-push and demandpush models. The second model should be considered as a more effective one as it is based on collaboration between scientific institutions and businesses. Innovative policies of many countries let us conclude that a demand-push model has a greater potential to boost economic development based on innovative ideas.